Wheat in growing-finishing rations - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Varying percentages of wheat replaced sorghum grain in rations for growing pigs in two trials. There were no significant differences in performance of pigs in trial one. In trial two significant differences unrelated to wheat in the diet occurred. Average feed efficiency for all groups receiving no wheat (100% sorghum) was 3.13 pounds. Average feed efficiency for all groups receiving no sorghum grain (100% wheat) was 3.31 pounds. Barrows gained 9% faster than gilts. Pelleting the ration saved an average of 49 pounds of feed for every 100 pounds of gain (17%).; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Wheat; Growing-Finishing rations; Pelleting